Titanic, o legado do grande navio: permanências e alterações no imaginário das catástrofes. - Sienna, Kleber (2018)
Since that fateful and chilly dawn of April 15, 1912, the world has witnessed the construction of larger ships, some already dismantled or lying, solitary, in the darkness of the bottom of the oceans and others still in circulation. There were also sea disasters involving more victims, such as SS Kiangya in 1948 and MV Doña Paz in 1987. However, no other ship has become as famous and significant for popular naval and imaginary history as the Royal Mail Ship Titanic. The RMS Titanic has entered into the imagery of navy, literature and cinema. He fed the dreams and nightmares of generations, from that of 1912 that was perplexed to receive the news of the disaster until our present generation that has it in the ambivalence of a feat of the engineering of its time, as well as a fruit of the arrogance of its idealizadores . This dissertation seeks to analyze the imagery caused by the construction and wreck of the Titanic and its mechanisms of maintenance and propagation throughout the twentieth and early twenty-first century through literary works that elect the great ship as thematic.